The Effect of Value Congruence Between Founder and Successor on Successor's Willingness: The Mediating Role of the Founder–Successor Relationship. (September 2019) - Lee, Jean S. K.; Zhao, Guozhen; Lu, Feifei
Drawing from social exchange theory, this article explores the founder–successor relationship quality as a mediated pathway in examining the effects of founder–successor value congruence on successor's willingness to take over the business. Based on survey data from 102 founder–successor dyads, polynomial regression analysis shows that when both a founder and a successor have high value congruence in family prosperity, the relationship quality will be enhanced, which leads to higher successor's willingness. When there is value incongruence between a founder and a successor, the successor's family prosperity value has a more important impact on the founder–successor relationship and successor's willingness.